Evaluation of immune profiles associated with control of mycobacterial growth in systemic lupus erythematosus (SLE) patients - Ongarj, J; Intapiboon, P; Surasombatpattana, S; Satti, I; Harris, SA; Morrison, H; Sophonmanee, R; McShane, H; Tanner, R; Pinpathomrat, N (Elsevier, 2024)
Tuberculosis (TB) is an infectious disease with the burden concentrated in low- and middle-income countries. Systemic lupus erythematosus (SLE) is an autoimmune disease associated with widespread inflammation that is prevalent in some TB endemic areas including East Africa and parts of Southeast Asia. SLE patients are known to be at higher risk of becoming infected with M. tb, developing TB disease. However, the immune mechanisms underlying this susceptibility are not well understood, particularly in the absence of immunosuppressive drugs. We present a pilot study in which we have evaluated intracellular cytokine responses and ex vivo ability to control mycobacterial growth using peripheral blood mononuclear cells (PBMC) collected from SLE patients before and during SLE treatment. After six months of treatment, SLE patients had the highest frequencies of CD8+ T cells, NK cells and NKT cells producing IFN-γ and/or TNF-α. This group also showed superior control of mycobacterial growth, and proinflammatory cytokine-producing NK and NKT cells correlated with mycobacterial growth inhibition at the individual patient level. These findings contribute to a better understanding of autoimmune profiles associated with control of mycobacterial growth in SLE patients, which may inform intervention strategies to reduce risk of TB disease in this population.